Effect of Bypass Fat Supplementation on Productive and Reproductive Performance of Crossbred Cows - Sihag, Sajjan; Sihag, Z S; Kumar, Sushil; Dhaka, S S; Patil, C S (Indian Journal of Animal Nutrition, 2020)
Objective of this study was to examine the effects of dietary bypass fat supplementation on the productive and reproductive performance of lactating cattle. Eighteen lactating crossbred (Holstein Friesian x Haryana x Sahiwal) cattle yielding 14Â±2.0 kg milk per day and 10-15 days in milk were divided into three groups on the basis of milk yield and parity. Group T1 was fed control diet. Concentrate mixture in groupT2 was added with 2.15 % vegetable oil while that of T3 was supplemented with 2.5% bypass fat. Â The DMI was similar in all 3 groups. Digestibility of dry matter, ether extract and organic matter were significantly (P<0.05) higher in group T3. Digestible fat, organic matter and TDN intake were significantly (P<0.05) more in group T3. Average daily milk production was higher by 8.72% in group T2 and 18.02% in group T3 as compared group T1. Average daily 4% fat corrected milk production in group T3 was 21.37% higher than in group T1. Fat content in milk was higher (P<0.05) in group T3 than T2 and T1, however, milk protein content remained unaffected. Bypass fat in the diet had positive effect on reproductive parameters. Net return over feed cost of 4% FCM yield was 30.37% higher in groupT3. It was concluded that supplementation of diet with bypass fat in early lactating crossbred cows increased milk and milk fat yield leading to higher net returns.